Divergence of craniofacial developmental trajectories among avian embryos. Issue 9 (2nd July 2015) - Smith, Francis J.; Percival, Christopher J.; Young, Nathan M.; Hu, Diane; Schneider, Richard A.; Marcucio, Ralph S.; Hallgrimsson, Benedikt; Cooper, Kimberly L.; Shapiro, Michael D.
<x xml:space="preserve">Abstract</x> Background: Morphological divergence among related species involves changes to developmental processes. When such variation arises in development has garnered considerable theoretical interest relating to the broader issue of how development may constrain evolutionary change. The hourglass model holds that while early developmental events may be highly evolvable, there is a phylotypic stage when key developmental events are conserved. Thus, evolutionary divergence among related species should tend to arise after such a stage of reduced evolvability and, consequently, reduced variation among species. We test this prediction by comparing developmental trajectories among three avian species of varying relatedness (chick, quail, and duck) to locate their putative point of divergence. Three‐dimensional geometric morphometrics and trajectory analyses were used to measure the significance of the facial shape variation observed among these species. Results: Duck embryos, being more distantly related, differed from the more closely‐related chick and quail embryos in the enlargement of their frontonasal prominences. Phenotypic trajectory analyses demonstrated divergence of the three species, most notably, duck. Conclusions: The results demonstrate that the two more closely related species share similar facial morphologies for a longer time during development, while ducks diverge. This suggests a surprising lability of craniofacial development during early face formation. Developmental Dynamics 244:1158–1167, 2015. © 2015 Wiley Periodicals, Inc.